Ultrasound findings in infertile women with endometriosis: evidence of concomitant uterine disorders. (1st September 2020) - Capezzuoli, Tommaso; Vannuccini, Silvia; Fantappiè, Giulia; Orlandi, Giulia; Rizzello, Francesca; Coccia, Maria Elisabetta; Petraglia, Felice
Abstract: Endometriosis is a gynecological disease characterized by pain and infertility. The diagnosis is very often made during the infertility work-up, together with other reproductive diseases and uterine disorders. A retrospective cohort study was conducted on infertile women with clinical or ultrasound suspect of endometriosis, undergoing an ultrasound (US) evaluation by a team of expert sonographers ( n  = 419), with the aim to evaluate the prevalence of concomitant uterine disorders. The US coexistence of endometriosis with uterine fibroids and/or adenomyosis was investigated according to three age intervals (<35years; 35 ≥ years <45; ≥45 years) and to endometriosis phenotypes: ovarian endometriosis (OMA), deep infiltrating endometriosis (DIE), or both. The US diagnosis of fibroids was made in 3.1% of cases, adenomyosis was found in 21.2%, and the co-existence of both uterine disorders with endometriosis was reported in 14.6% of patients. When analyzed according to age, patients aged >35 years were more likely to be affected by uterine fibroids ( p  = .003), adenomyosis ( p  = .030) and both adenomyosis and fibroids ( p  < .0001). No statistically significant association was found between endometriosis phenotypes and myometrial pathologies. Uterine disorders coexistence should be considered in the assessment of women with endometriosis, in order to better define a treatment strategy for infertility, especially in women older than 35 years.